Evaluating the Role of Paracetamol in Alleviating Symptoms of Upper Respiratory Infections - Kalsoom, Aumara Bibi, Amara Saif, Syed Hyder Raza, Rao Abubakar, Muhammad Umair Masood, Azfar Athar Ishaqui (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Fever is a very common adaptive immune response in acute respiratory tract disorders during infancy. Antipyretic / analgesic drugs such as paracetamol (acetaminophen) are widely used to improve the comfort of the child. Objective: To determine the efficacy of paracetamol in symptomatic relief of upper respiratory tract infections in children aged 2 to 5 years. Study Design: Descriptive case series Study Setting: Department of Pediatrics, Ayub Teaching Hospital, Abbottabad Duration of study: Six months from October 13, 2020, to April 13, 2021 Subjects and methods: All children aged 2 to 5 years of either gender having upper respiratory tract infections and duration of symptoms of >2 days were consecutively enrolled. Patients were prescribed Paracetamol in a dose of 10 mg/kg/dose 6 hourly for 3 days. Patients were followed up after 3 days to see the efficacy of Paracetamol in symptomatic relief of upper respiratory tract infections. Results: Of 284 children, the mean age of the children was 4.01 ±1.10 years. There were 135 (47.5%) males and 149 (52.5%) females. The mean weight of the children was 12.36 ±3.42 kg. The mean duration of symptoms was 5.11 ±0.95 days. The efficacy of paracetamol in symptomatic relief of upper respiratory tract infection was found to be 184 (64.8%). A non-significant difference of efficacy of paracetamol was observed with age (p-value 0.578), gender (p-value 0.908), weight (pvalue 0.586), and duration of symptoms (p-value 0.872). Practical Implication: This study was planned to determine the efficacy of paracetamol in symptomatic relief of upper respiratory tract infections. The results of this study could be used in owing to locally produced evidence. Conclusion: The efficacy of paracetamol was observed in 64.8% children aged 2 to 5 years with symptomatic relief of upper respiratory tract infections in children. Keywords: Efficacy, Paracetamol, Children, Upper Respiratory Tract Infections